Digital Marketing Communication Strategy - Rizaldi, Arjuna; Hidayat, H (Universitas Ciputra Surabaya, 2020)
The purpose of this research is to see how digital marketing strategies can affect the increase in sales and number of customers. The method used to support this research is descriptive qualitative method by collecting data through literature study in order to describe the elements that exist in a digital marketing strategy in depth. The results of this study show that the development of information technology is necessary for the community to support a variety of business activities both large and small. one of them is using digital marketing in the marketing system of a business unit to increase sales volume and the number of consumers that affect competitiveness in global competition. It is because technology will facilitate human work in meeting their needs related to the development of business units.